Analysis of Financial Feasibility of Shuttle Transport Within The Province (AJDP) Denpasar Buleleng Route (Case Study: Minibus Colt L-300 Adhi Transport) - Wedagama, Dewa Ayu Trisna; I Nyoman Indra Kumara (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
One of the AJDP service providers in Bali is Adhi Transport which has 3 fleets on the Denpasar-Buleleng route. The aim of the research is to determine vehicle operating costs, income and analyze the level of financial feasibility of transportation operations. The data used in this research includes secondary data (company financial data) obtained through interviews and questionnaire surveys with agencies. The main indicators to pay attention to are NPV, BCR, and IRR. The results obtained are vehicle operating costs of Rp. 334,108,000/year, income Rp. 6223,100,000/year. The NPV value is IDR. 634,943,527 > 0, BCR 1.17 > 1, and IRR 42.99% > 16%. The conclusions obtained from the results of the investment analysis are financially feasible.